Multiple reasons underlaying uncontrolled disease in the majority of chronic rhinosinusitis patients - Viskens, An-Sofie; Wils, Tine; Van Bulck, Pauline; Cools, Leen; Vanderveken, Olivier; Hellings, Peter W. (Frontiers in Allergy, 2022)
Background Up to 40% of patients with chronic rhinosinusitis (CRS) remain uncontrolled despite guidelines of care being available, with an enormous socio-economic impact. The reasons for uncontrolled disease can be arbitrarily divided into disease-related, diagnosis-related, treatment-related, and patient-related factors. The relative contribution of each factor in uncontrolled CRS remains speculative. This explorative study aimed at determining the factors responsible for uncontrolled CRS in a tertiary care center, thereby identifying the most commons reasons for uncontrolled disease in CRS. Methods Patients with uncontrolled CRS (n = 187) were asked to fill out a questionnaire and underwent a clinical examination at the outpatient clinic of the University Hospital of Leuven, Belgium. Two independent physicians evaluated the (multiple) reason(s) for uncontrolled disease. Results In uncontrolled CRS, 66% of patients showed two or more reasons for uncontrolled disease according to the physicians' evaluation. Disease-related factors (70%) were most often considered the reason for uncontrolled disease, followed by treatment- (45%), patient- (42%), and diagnosis- (32%) related factors. Conclusion In case of uncontrolled CRS, the different contributing factors to the uncontrolled nature need to be carefully addressed during diagnostic and therapeutic actions in order to define strategies to improve CRS care. Most uncontrolled CRS patients have multiple reasons contributing to their disease status, with disease-related factors being the most common factor.